TELAAH NORMATIF DAN EMPIRIS TENTANG IMPLEMENTASI ASAS DEKONSENTRASI DI INDONESIA (THE NORMATIVE AND EMPIRICAL STUDY ABOUT THE IMPLEMENTATION OF THE PRINCIPLE OF DECONCENTRATION IN INDONESIA) - Tri Widodo W. Utomo (Jurnal Borneo Administrator, 2012)
Deconcentration is one of the most important principles in managing central-local relationship in a unitary state. Together with decentralization and assistance task principles, deconcentration reveals the best strategy to assure the integrity of the state. In the Indonesian context, however, there is a tendency that decentralization is getting stronger, while deconcentration is moving to the opposite direction. This paper tries to elaborate the norm and the practice of deconcentration in Indonesia, and the possibility to construct an equilibrium concept between decentralization and deconcentration.  Keywords : deconcentration, decentralization, Indonesia.Dekonsentrasi adalah salah satu asas terpenting dalam pengelolaan hubungan pusat-daerah di sebuah negara kesatuan. Bersama dengan desentralisasi dan tugas pembantuan, dekonsentrasi merupakan strategi terbaik dalam menjamin integritas negara. Dalam konteks Indonesia, terdapat kecenderungan bahwa asas desentralisasi semakin menguat, sementara asas dekonsentrasi berjalan menuju arah berlawanan. Tulisan ini mencoba mengelaborasi sisi normatif dan empiris dalam implementasi asas dekonsentrasi di Indonesia, dan kemungkinan untuk mengembangkan ide keseimbangan antara desentralisasi dan dekonsentrasi.  Kata kunci: dekonsentrasi, desentralisasi, Indonesia.